KOMODITAS UNGGULAN DAN POTENSI DAYA SAING SEKTOR PERTANIAN KABUPATEN KEPULAUAN MENTAWAI - Syahrial Syahrial (Jurnal Agribisnis Indonesia, 2026)
The agricultural sector serves as a strategic pillar in fostering economic growth, especially in rural areas that heavily depend on agricultural activities. This study endeavors to assess the competitiveness of the agricultural sector through the identification of regional leading commodities. The analytical methods used include Location Quotient, Specialization Coefficient, Localization Coefficient, Dynamic Location Quotient, and Shift Share Analysis. This research employs secondary data on the production value of agricultural commodities, which include three main subsectors: food crops, horticulture, and plantations, obtained from Mentawai Islands Regency and West Sumatra Province for the period 2020 to 2024. The analysis results indicate that several commodities in Mentawai Islands Regency are categorized as leading commodities. In the food crops subsector, these commodities include cassava and sweet potatoes; in the horticulture subsector, bananas and duku (a type of tropical fruit); and in the plantation subsector, coconut, cloves, and nutmeg. However, based on the results of specialization and localization analysis, no commodity in the agricultural sector showed characteristics of specialization or localization in Mentawai Islands Regency. In terms of potential commodity development in the future, sweet potatoes are expected to remain dominant in the food crops subsector, while cassava is no longer considered a leading commodity. In the horticulture subsector, bananas and duku are expected to retain their status as leading commodities. In the plantation subsector, only nutmeg is projected to maintain its competitive advantage. Based on the competitive advantage analysis, it is found that has commodities with strong competitiveness, namely coconut and areca nut (pinang).